Internalization of Multicultural Values Through Islamic Religious Education in Secondary School Students - Suwarno Djodding; ST. Wardah Hanafie Dos (Prodi PAI STIT Sunan Giri Bima, 2026)
This study examines the internalization of multicultural values through the learning of Islamic Religious Education (PAI) in secondary school students with a descriptive qualitative approach. Data were collected through interviews, observations, and documentation in several public and vocational high schools in Indonesia. The results of the study show that PAI plays a strategic role as a pedagogical instrument in forming attitudes of tolerance, mutual respect, and inclusivity of students when implemented contextually and dialogically. The novelty of this research lies in the affirmation that the effectiveness of internalizing multicultural values is not only determined by the teaching material, but also by the ideological awareness of teachers, school policy support, and the integration of curricular and extracurricular activities. These findings strengthen PAI's position as a vehicle for strengthening religiosity with a humanitarian perspective in the midst of the reality of a multicultural society. The implications of this study reinforce the urgency of integrating multicultural values in PAI learning as a strategy to increase social harmony in diverse school environments.